Use of alkaline process for the extraction of gelatin from the river jellyfish, Acromitus hardenbergi Stiasny, 1934 - Omar, Wan Nur Atikah (2012)
The aim of this study was to investigate the effect of pre-treatments time and extraction temperatures by characterizing the jellyfish gelatin obtained using gelatin yield, proximate composition, amino acid composition, organoleptic characterizations and micrograph using scanning electron microscopy. Gelatin was extracted from edible jellyfish species, Acromitus hardenbergi by alkaline process at different of pre-treatment time (7, 10, 14 and 17 days) and heating temperatures (40ºC and 55ºC). The study indicates that the highest gelatin yield based on wet, dry and protein basis obtained from 14 day pre-treatment using 40ºC extraction temperature were 0.56%, 34.93% and 66.54%, respectively. However, analyses showed no significant differences in yield based on wet, dry and protein basis when compared with jellyfish gelatin obtained at 40ºC using 7 day of pre-treatment. The highest protein content was produced at 55ºC with 7 day of pre-treatments (88.22%). Glycine became the major amino acid in jellyfish gelatin in all treatments. Analyses showed no significant differences in glycine content of jellyfish gelatin extracted at 40ºC using 14 day of pre-treatment and at 55ºC using 7, 14 and 17 days of pre-treatment when compared with porcine gelatin (P > 0.05). The highest content of glycine, hydroxyproline and proline were obtained using 55ºC at 7 days of pre-treatment. Colours of jellyfish gelatin in all treatments were significantly different (P < 0.05) from each other and colour ranged from white, snowy white, creamy white to brownish. Brownish colour of jellyfish gelatin obtained from 55ºC at 7 days of pre-treatment was almost similar as bovine skin gelatin. Micrograph showed porous components within jellyfish gelatin from 40ºC (7, 10 and 17 pre-treatment days) and 55ºC (14 pre-treatment days) and their morphology were quite similar. The study showed there were complex interaction between temperature and pre-treatment days which affect the biochemical characteristics of jellyfish gelatin. This study indicates that alkaline method can be used to extract gelatin from jellyfish.